Tinjaun Ketepatan Kode Diagnosis Pasien Diabetes Mellitus Rawat Inap dengan Lama Rawat - Wini Wini; Deasy Rosmala Dewi; Daniel Happy Putra; Nanda Aula Rumana (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
The accuracy of the diagnosis code is the conformity between the diagnosis code determined by the coder and the patient's medical record, in accordance with ICD-10 rules. Length of stay is a term used in a hospital that describes the length of time a patient is treated as measured in days and is one aspect of care and service at the hospital. The aim of the study was to find out the description of the accuracy of the diagnosis code for inpatient diabetes mellitus patients with length of stay at the Islamic Hospital of Jakarta Pondok Kopi. The research method uses a quantitative descriptive. The results of the research on Standard Operating Procedures (SPO) which regulate the determination of codes in inpatient care already exist, but there is no specific coding for diabetes mellitus. For the length of stay of diabetes mellitus patients 3-5 days, the percentage of correctness of diabetes mellitus diagnosis codes for inpatients at the Jakarta Islamic Hospital Pondok Kopi in 2022 resulted in 40 medical records (48.20%) diagnosis codes and 40 medical records (48.20%) inaccurate diabetes mellitus diagnosis codes 43 medical records (51.80%). Suggestions in this study the head of medical records submits an update of the SPO regarding coding and specifically so that the results of the work go according to the applicable and effective policies, an increase in the number of medical records officers in the coding section and communication between the coding officer and the doctor giving the diagnosis needs to be improved in order to produce a code right.